Acbp is essential for decidualization during early pregnancy in mice. Issue 5 (29th March 2022) - Zhang, Xue; Tan, Bo-Yin; Zhang, Shuang; Feng, Qian; Bai, Ying; Xiao, Shi-Quan; Chen, Xue-Mei; He, Jun-Lin; Liu, Xue-Qing; Wang, Ying-Xiong; Ding, Yu-Bin; Li, Fang-Fang
Abstract : Decidualization of uterine stromal cells plays an important role in the establishment of normal pregnancy. Previous studies have demonstrated that Acyl-CoA binding protein ( Acbp ) is critical to cellular proliferation, differentiation, mitochondrial functions, and autophagy. The characterization and physiological function of Acbp during decidualization remain largely unknown. In the present study, we conducted the expression profile of Acbp in the endometrium of early pregnant mice. With the occurrence of decidualization, the expression of Acbp gradually increased. Similarly, Acbp expression was also strongly expressed in decidualized cells following artificial decidualization, both in vivo and in vitro . We applied the mice pseudopregnancy model to reveal that the expression of Acbp in the endometrium of early pregnant mice was not induced by embryonic signaling. Moreover, P4 significantly upregulated the expression of Acbp, whereas E2 appeared to have no regulating effect on Acbp expression in uterine stromal cells. Concurrently, we found that interfering with Acbp attenuated decidualization, and that might due to mitochondrial dysfunctions and the inhibition of fatty acid oxidation. The level of autophagy was increased after knocking down Acbp . During induced decidualization, the expression of ACBP was decreased with the treatment of rapamycin (an autophagy inducer), while increased with the addition of Chloroquine (an autophagy inhibitor). Our work suggests that Acbp plays an essential role in the proliferation and differentiation of stromal cells during decidualization through regulating mitochondrial functions, fatty acid oxidation, and autophagy.